Between the Flames of the Past and the Present: The Challenges to the Preservation of Ouro Preto (Revista Angelus Novus, 2023)
This paper analyses the historic site of Ouro Preto and aims to understand the challenges posed to its preservation from the 1980s to the early 2000s, i.e., the period when it was designated a World Heritage Site by UNESCO. Due to the accelerated process of decharacterization and degradation of the heritage, several difficulties are posed to the preservation of the site. Therefore, we stress the fire at Pilão Hotel in 2003 and its repercussions on the movement Chama: Awareness and Prevention against Fire and the issues concerning the possible impacts on the status granted by UNESCO.